Complication on Premature Rupture of Membrane in Intrapartum Mother Infected with COVID-19: Meta-Analysis - Ningsih, Hepti Widia; Murti, Bhisma; Budihastuti, Uki Retno (Journal of Epidemiology and Public Health, 2022)
Background: Pregnant women and fetuses are populations that are at high risk of being infected with the virus. COVID-19 in pregnant women is considered a risk factor for causing complications in pregnancy such as premature rupture of membranes. This study aims to analyze complications of premature rupture of membranes in mothers infected with COVID-19. Subjects and Method: This was a systematic review and meta-analysis. Article searches were conducted using electronic databases such as Google Scholar, PubMed and Science Direct. The articles used are articles published from 2020-2022. Keywords to search for articles were: “COVID-19” OR “2019-nCoV” OR “novel coronavirus” OR “SARS-CoV-2” OR “coronavirus 2” AND “premature rupture of membrane” OR “prelabour rupture of membrane” AND “pregnancy.” The inclusion criteria used were full text articles in English with a cohort study design, multivariate analysis with Adjusted Odds Ratios (aOR), research subjects were pregnant women, intervention was COVID-19 infection, comparison was not infected with COVID-19 , the outcome of the study was premature rupture of membranes.The results of the search for articles were included in the PRISMA diagram and analyzed using the Review Manager 5.3 application. Results: A total of 9 cohort study articles from the United States, Bangladesh, China, India, Mexico, Romania, and Spain were selected for systematic review and meta-analysis. The results showed that pregnant women infected with COVID-19 had a risk of complications of premature rupture of membranes as much as 2.26 times compared to pregnant women who were not infected with COVID-19 and the results were statistically significant (aOR = 2.26; 95% CI = 1.33 to 3.82; p = 0.002). Conclusion: Pregnant women infected with COVID-19 increase the risk of premature rupture of membranes. Keywords: COVID-19, pregnancy, premature rupture of membranes, meta-analysis Correspondence: Hepti Widia Ningsih. Masters Program in Public Health Universitas Sebelas Maret, Jl. Ir, Sutami 36A, Surakarta 51726, Central Java. Email: heptiwidian@gmail.com. Mobile +6285729442615.